The combined Shepard operator of inverse quadratic and inverse multiquadric type - CĂTINAȘ, Teodora; MALINA, Andra (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
Starting with the classical, the modified and the iterative Shepard methods, we construct some new Shepard type operators, using the inverse qua- dratic and the inverse multiquadric radial basis functions. Given some sets of points, we compute some representative subsets of knot points following an algorithm described by J.R. McMahon in 1986. Mathematics Subject Classification (2010): 41A05, 41A25, 41A80. Received 27 January 2022; Accepted 4 April 2022.